Medicinal Plant Images - Cock, Dr. I E (Asian Journal of Biological and Life Sciences)
Tasmannia lanceolata (Poir) A. C. Sm. (family Winteraceae), commonly known as Tasmanian pepper or mountain pepper berry, is shrub which is endemic to the woodlands and cool temperate rainforests of Tasmania and the south-eastern region of the Australian mainland. The leaves, berries and bark of this plant have traditional uses as a food flavouring, and as a medicinal plant. Australian Aborigines used T. lanceolata as a therapeutic agent to treat stomach disorders and as an emetic, as well as general usage as a tonic.1 That study reported that T. lanceolata was used by Australian Aborigines for the treatment and cure of skin disorders, venereal diseases, colic, stomach ache and as a quinine substitute. Several of these traditional uses have been validated in recent publications. The antibacterial properties of T. lanceolata have been particularly well reported against a wide variety of bacterial species.2- 6 Similarly, the related species Tasmannia stipatata7 and Pseudowintwera colorata (Raoul) Dandy8 have also been reported to inhibit the growth of multiple bacteria. T. lanceolata extracts have also been reported to inhibit the growth of the gastrointestinal protozoal parasite Giadria duodenalis.6,9 Similar extracts also inhibit the proliferation of several human cancer cell lines.6,10 The photograph was taken in the Royal Tasmanian Botanical Gardens, Hobart, Australia by Dr Ian Cock in January 2022.